I-V Characteristics of GaAs/AlAs Asymmetric Spacer Layer Tunnel Diode (ASPAT) Using Statistical Validation - E. Jamil; N. A. AzizulRahman; M. Othman; S. A. Rahman; W. Z. Wan Ismail; K. N. Z. Ariffin (Journal of Science and Technology, 2025)
The Asymmetric Spacer Layer Tunnel Diode (ASPAT) has been physically fabricated and simulated using (2) Silvaco Atlas, a widely used semiconductor device simulation software. The ASPAT features an asymmetrical structure, leading to asymmetric current-voltage (I-V) characteristics, making it suitable as a zero-bias detector with low power consumption for high-frequency applications. Accurately validating these characteristics is critical to assessing the device’s performance. However, existing numerical models rely on the Poisson, Schrödinger, and Tsu-Esaki equations, which only account for tunnelling behaviour in discrete regions emitter, barrier, and collector without fully incorporating the effects of doping concentration, material composition, and interface defects. The Transfer Matrix Method (TMM), while addressing some limitations, assumes perfect interfaces, which may not always be the case in three-dimensional (3D) fabricated devices. This study aims to investigate the numerical models used for ASPAT diode design, identify their limitations, propose an improved numerical model, and validate the proposed model against existing methods. The fabrication process of the ASPAT diode involves molecular beam epitaxy (MBE) for the Gallium Arsenide/Aluminum Arsenide (GaAs/AlAs) structure, followed by metal contact deposition, with detailed consideration of doping concentrations and potential material mismatches at the interfaces. Statistical validation of experimental and simulated I-V characteristics is conducted using linear regression, non-linear regression, and hypothesis testing of slope and intercept coefficients. (1) To ensure accuracy, a 5% significance level is assumed for validation. Results indicate that the experimental and simulation data align within a justified 5% error margin, confirming ? 95% validation accuracy to confirm the perfect validation despite of several limitations in physical simulation. However, the impact of 3D structural effects, boundary defects, and thermal influences must be further examined to enhance ASPAT performance. This study provides a refined numerical approach to improving ASPAT diode characterization for optimized design and performance evaluation.